2005
DOI: 10.1159/000088016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Interleukin-18 by Direct Hemoperfusion with Polymyxin B-Immobilized Fiber in Patients with Septic Shock

Abstract: Background/Aims: Polymyxin B-immobilized fiber (PMX-F) treatment is reported to be safe and effective in patients with severe sepsis and septic shock. The aim of the present study was to determine whether plasma levels of interleukin (IL)-18, which is linked with sepsis, are associated with plasma endotoxin levels and sepsis-related scores and whether PMX-F treatment affects these variables in patients with septic shock. Patients and Methods: Twenty-six patients with septic shock (15 men and 11 women; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The blood levels of some inflammatory chemokines, e.g. metalloproteinase 9, tissue inhibitor of metalloproteinase 1 [4], neutrophil elastase, IL-8 [46] and IL-18 [47], are immediately decreased in ARDS patients after PMX-DHP. Seo et al [18] have reported that IL-6, IL-8 and plasminogen activator inhibitor 1 are decreased in patients with rapidly progressive IP who responded to PMX-DHP.…”
Section: Discussionmentioning
confidence: 99%
“…The blood levels of some inflammatory chemokines, e.g. metalloproteinase 9, tissue inhibitor of metalloproteinase 1 [4], neutrophil elastase, IL-8 [46] and IL-18 [47], are immediately decreased in ARDS patients after PMX-DHP. Seo et al [18] have reported that IL-6, IL-8 and plasminogen activator inhibitor 1 are decreased in patients with rapidly progressive IP who responded to PMX-DHP.…”
Section: Discussionmentioning
confidence: 99%
“…PMX is also therapeutic in and of itself: removing endotoxins improves the shock, but does not remove the etiological agents. We and other investigators have reported that PMX-F is effective in reducing various inflammatory mediators in patients with septic shock [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…All blood and urine samples were stored at (808C prior to assay. Blood endotoxin levels were determined by Endospecy test [10,12,13], the normal upper limit being 9.8 pg/ml. Twenty-four hour urine samples obtained starting at 1100h until the next day at 1100h were collected from patients in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that PMX-F treatment is effective in reducing various mediators, including serum interleukin-6, interleukin-18, soluble interleukin-2 receptor [12,13]. However, the effect of PMX-F treatment on urinary 8-OHdG levels in septic shock patients is unknown.…”
Section: Introductionmentioning
confidence: 99%